The Correlation Between Interleukin-6 (IL-6) Levels and the Extent of Coronary Lesions Based on SYNTAX Scores in Patients with Acute Coronary Syndrome (ACS) - Siallagan, Delpiana; Loesnihari, Ricke; Hasan, Refli (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: Atherosclerosis plays an important role in the pathogenesis of acute coronary syndrome (ACS). Inflammation plays a causal role in atherosclerosis. There are many inflammatory markers related to ACS, including C-reactive protein (CRP), homocysteine, matrix metal loproteinases, interleukin (IL)-6, IL-8, and IL-27. IL-6 is the sign of synthesis of acute phase proteins. Recently, the clinical trials related to ACS showed that IL-6 may be an indicator of increased risk for ACS. An Interleukin-6 (IL-6) examination is can be used to assess risk factors for acute coronary syndrome (ACS). Interleukin-6 is a marker of local inflammation of coronary plaque and peripheral blood circulation which increases the occurrence of coronary heart disease causing plaque instability and rupture. The SYNTAX scoring system has correlation assessed through angiography assessing the complexity of the severity of coronary artery stenosis. This study aims to determine the between Interleukin-6 (IL-6) levels and the extent of coronary lesions based on the SYNTAX score in patients with acute coronary syndrome (ACS).Methods: This is a cross-sectional study of 45 patients with acute coronary syndrome (ACS) who were treated at H. Adam Malik General Hospital, Medan (February 2023 – May 2023). IL-6 levels were examined using the Electrochemiluminescent Immunoassay (ECLIA) method using Cobas e 411. The extent of the coronary lesion was calculated based on the SYNTAX score from coronary angiography which was calculated by two invasive cardiologist as suggested before using an online calculator. We used the Spearman correlation test and Mann Whitney test to analyze the data.Results: There were 39 male subjects (86.7%) total. The mean age of the subjects was 54.89 ± 10.3 years old. Most of the subjects experienced STEMI in total 28 people (62.2%). The Median IL-6 levels was 19.22 pg/mL while the median of SYNTAX score level was 13.00. By using cross-sectional study and the spearman correlationa test, there is a significant correlation between IL-6 and the SYNTAX score with the correlation value obtained r = 0.343 (p = 0.021).Conclusion: There is a significant relationship between IL-6 and the extent of coronary lesions based on the SYNTAX score in patients with acute coronary syndrome.